2015
DOI: 10.1590/1983-084x/14_036
|View full text |Cite
|
Sign up to set email alerts
|

The insecticidal potential of Foeniculum vulgareMill., Pimpinella anisum L. and Caryophillus aromaticus L. to control aphid on kale plants

Abstract: ABSTRACT:The use of natural substances for pest control in agriculture is, economically, a viable option and has benefits for both the humanbeing and the environment, due to its low persistence and toxicity. Thus, this trial aimed on determining the insecticidal potential of the extracts and essential oils of fennel (Foeniculum vulgare Mill.), anise (Pimpinella anisum L.) and clove (Caryophillus aromaticus L.) to control Brevicoryne brassicae L. in kale (Brassica oleracea var. acephala DC.). The treatments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
(11 reference statements)
0
8
0
1
Order By: Relevance
“…In the rest of the world, 139 plant species representing 44 families [ 149 , 153 , 154 , 156 , 166 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ,…”
Section: Resultsunclassified
“…In the rest of the world, 139 plant species representing 44 families [ 149 , 153 , 154 , 156 , 166 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ,…”
Section: Resultsunclassified
“…Anethole (ANT), or trans -anethole, is an organic compound frequently used as flavoring substance. It belongs to the family of phenylpropanoids (C 6 –C 3 ), a class of aromatic compounds that occurs widely in essential oils [ 204 , 205 ]. ANT is the main constituent of many essential oils [ 206 ], such as Illicium verum [ 207 ] and Pimpinella anisum [ 208 ], and seems to play a key role in the biological effects attributed to these oils.…”
Section: Resultsmentioning
confidence: 99%
“…Tetranychus urticae , Dermatophagoides farinae and Dermatophagoides pteronyssinus [ 13 , 14 ]. Also, fennel found to have insecticidal activity against the sheep ked Melophagus ovinus [ 15 ] and the aphid nymphs [ 17 ]. Fennel EO was also proven to be highly toxic to two important insect pests of the stored product ( Sitophilus oryzae and Callosobruchus Chinensis ) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was found to have insecticidal activity against Melophagus ovinus sheep ked [ 15 ], and larvicidal activity against Culex pipiens mosquito [ 16 ]. Moreover, Lucca et al [ 17 ] reported 70% mortality rate in aphid nymphs treated with 1% fennel oil.…”
Section: Introductionmentioning
confidence: 99%